Viability of the proposed alternative refrigerants as future refrigerants - Usman, Abdullahi; Priyadarshini, Saigeeta; Mishra, Akanksha; Singh, Pramod K.; Adam, Ahmad Muhammad; Payal, Himanshu; Noor, I. M. (John Wiley and Sons, 2025)
Globally, the need of future refrigerant is becoming important to save the environment owing to the increase of urbanization and industrialization. The rate of accumulation of greenhouse gasses (GHG) from refrigerants depends on the rate of increase in urbanization and industrialization. However, the candidature of different classes of refrigerants to the stage of future refrigerants has been hindered by different challenges. Hence, the developments achieved in eliminating the various challenges has been studied through literature and the viability status of those classes of refrigerants has been improvised on the basis of green refrigeration, thermodynamic properties, performances and system design approaches. This paper reviews viability of most recently proposed refrigerants as future refrigerants. Hydrofluoroolefin (HFO) is the most viable class of refrigerants because of improvements noted in the challenges that hinder its future scope. Carbon dioxide (R-744) has also a viable scope of future refrigerants under controlled operating condition. In addition to that for ultra low temperature (ULT) refrigeration system, R-170, R-1132a, and R41 have been considered as most viable refrigerants.